A study on the density shoulder formation in the SOL of H-mode plasmas. (August 2017) - Carralero, D.; Madsen, J.; Artene, S.A.; Bernert, M.; Birkenmeier, G.; Eich, T.; Fuchert, G.; Laggner, F.; Naulin, V.; Manz, P.; Vianello, N.; Wolfrum, E.; et al.
Highlights: The formation of a density shoulder has been observed in inter-ELM H-mode plasmas. There is a link between shoulder formation and filament transition. Divertor collisionality remains the necessary condition for the shoulder formation. An additional condition has been found, related to deuterium fueling. Overall, the shoulder formation mechanism observed in L-mode remains valid. Abstract: The term "shoulder formation" refers to an increase of the density decay length in the scrape-off layer (SOL) observed in many tokamaks during L-mode operation when a density threshold is reached. Recent experiments in ASDEX Upgrade (AUG) and JET have shown that the shoulder forms when the divertor collisionality in the divertor electrically disconnects filaments from the wall. This leads to a transition from the sheath limited to the inertial regime and to an enhancement of radial particle transport, in good agreement with analytical models. In the present work, the validity of such a mechanism is investigated in the more reactor-relevant H-mode regime. For this, a cold divertor H-mode scenario is developed in AUG using different levels of D puffing and N seeding, in which inter-ELM filaments and SOL density profiles are measured. The basic relation between filament size and divertor collisionality is still valid in H-mode plasmas, albeit an additional condition related to the gas fueling rate has been found for the formation of the shoulder.